Mandatory audit firm rotation: A student perspective An assessment of the perceived impact on auditor independence - Msizi Gwala; Bomi Cyril Nomlala (Jurnal Akuntansi dan Auditing Indonesia, 2021)
Mandatory Audit Firm Rotation (MAFR), set to be implemented in South African from 1 April 2023, is poised by its propellers the world over as an essential reform in the efforts to improve auditor independence. Available literature suggests that there is no consensus regarding the impact of the implementation of MAFR. The divergent views on MAFR were demonstrated in recent time, with the European Union (EU) choosing to adopt it, while regulators in the United States decided to reject it. This paper examines the perspective of university auditing students on MAFR by examining the perceived impact it could have on auditor independence. The study finds that the majority (from 413 participants) of students surveyed are of the view that MAFR would yield positive outcomes on independence. The majority, however, agree on the MAFR Independence Benefit but warn about the possible negative consequences. MAFR will strengthen the independence of auditors.